The association between neuroticism personality traits and depressive psychopathology with quality of life among diabetic patients - Muhammad Meor O,; Hatta Sidi,; Woon, Luke Sy-Cherng; Farris Iman Leong A,; Farah Deena AS, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Diabetes mellitus (DM) is a chronic medical condition associated with psychological sequelae like depression and linked with specific personality traits. This study researched on quality of life (QoL) among patients with DM and its association with mood symptoms and personality traits. 291 diabetic respondents were recruited, where their socio-demographic data and other relevant profile were collected using the Beck Depression Inventory II (BDI-II), Generalized Anxiety Disorder scale (GAD-7), Big Five Inventory (BFI) and World Health Organization Quality of Life Instrument-Short Form questionnaire (WHOQoL-BREF). The mean age of the respondents was 60.43 years with approximately half of the respondents being males and married. Most respondents have been diagnosed with type 2 diabetes (N = 261, 89.7%) and the median duration of diabetes diagnosis was 14.17 years (SD = 9.72). The association between personality traits, psychological complications, and QoL after adjusting for demographic, personal, and clinical characteristics were studied. Based on the multiple linear regression models, after adjusting for age, employment, education status, monthly income, perceived social support, duration of DM and other variables, we found that the neuroticism (BFI) and mean BDI score was associated with poorer QoL, respectively. 1-unit increase in these two variables leading to 3.5- and 0.6-point decrease in QoL, (-3.465 (95% confidence interval, CI -5.788 to -1.143) and -0.560 (95% CI -0.779 to -0.341)) with p<0.001, respectively. An intervention focusing on the neuroticism and elevating the depressive psychopathology would help in the psychological management of patients with DM.